Performance Measurement Of Stunting Management Policy Implementation In Batam City - Diah Ayu Pratiwi; Sri Mulyati (Kemudi, 2023)
This study analyzes the performance measurement of stunting prevention policy implementation in Batam City by taking a case study of Integrated Stunting Prevention Convergence Policy Implementation in Batam City. The Batam City Government has implemented an integrated stunting prevention convergence policy to accelerate the reduction of stunting in Batam City since 2021. This study uses a qualitative research method with data collection techniques using in-depth interviews, observation, and documents. Selection of informants using a purposive sampling technique. The results of the study found that the performance of integrated stunting prevention convergent policy implementation in Batam City has been going well in achieving its goals because 0f the results of the policy output assessment, namely access; scope; frequency; service promptness; and the suitability of the program with the needs has been going well in its implementation. However, this policy still has deficiencies in terms of outreach to the public about stunting.